Iterative methods for solving equilibrium problems, variational inequalities and fixed points of nonexpansive semigroups - Prasit Cholamjiak (2018)
In this work, strong convergence theorems by the viscosity approximation method associated with Meir-Keeler contractions are established for solving fixed point problems of a nonexpansive semigroup, a system of equilibrium problems and variational inequality problems in a real Hilbert space. Further, applications related to commutative semigroup are obtained. © 2012 Springer Science+Business Media New York.